The Concept of Performance in Determining Annual Financial Result - SIMIONESCU, Silvia (Journal of Advanced Research in Management; Vol 7 No 1 (2016): JARM Volume VII Issue 1(13) Summer 2016DO - 10.14505//jarm.v7.1(13).03, 2017)
It often speaks of performance. But it is known, meaning that concept? We note that, despite the abundance of uses, performance is rarely defined, even in situations where it is the central object of study. Moreover, neither the origin of this concept is not widely presented. The meaning of the concept of performance has changed over time. He is a polysemous term, with various meanings depending on the areas where it is used. This explains why we speak of economic performance, economic and financial performance and financial performance. The concept of performance of the company is based on the theory of the stakeholders. Managers can not maximize firm value ignoring the interests of the social partners: shareholders, employees, creditors, by Ads" href="#8230787"> suppliers , customers, state, etc. From the perspective of the enterprise, these interests may be contradictory, which may give rise to conflicts within the organization, adversely affecting financial results.